EVALUATION OF VISUAL ACUITY THROUGH THE APPLICABILITY OF THE SNELLEN TEST IN PATIENTS: A LITERATURE REVIEW - Rodrigues da Silva, Natália; Casado de Freitas Silva, Rosany; da Silva Santos, Samara; Kelly da Silva Nascimento, Yohana; Costa Soares Silva, Talita; Ellen Costa Vasconcelos, Eduarda; Torres Di Pace Maranhão, Solange; Beatriz de Andrade Silva, Maria; Carvalho Santana, Fabio; Carolina Salustino, Maria; Allyson Gomes Ferreira, Jefferson (Health and Society, 2023)
Introduction: Elderly people with visual impairment tend to be more sedentary, with consequent muscle loss, balance and functionality. These factors end up leading to a decrease in the quality of life, restricting social participation by limiting activities. Objective: to evaluate, through scientific evidence, the importance of assessing visual acuity in the elderly. Methodology: The search was carried out by searching the following databases: Online Medical Literature Analysis and Retrieval System (MEDLINE®), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF). The keywords used followed the description of the terms Health Science Descriptors (DeCS) and Medical Subject Heading (MESH) in Portuguese, which are: visual acuity, elderly. In order to carry out the integrated search, the “and” connective was used, uniting the descriptors. At this stage, there was no use of other filters in order to address all the available literature within the focus of interest. Results: Initially, a table was built to expose the studies containing information such as year, title, authors and place of publication. After searching the databases through the established inclusion and exclusion descriptors, 08 articles were selected in (Chart 1) for anal Introduction: Elderly people with visual impairment tend to be more sedentary, with consequent muscle loss, balance and functionality. These factors end up leading to a decrease in the quality of life, restricting social participation by limiting activities. Objective: to evaluate, through scientific evidence, the importance of assessing visual acuity in the elderly. Methodology: The search was carried out by searching the following databases: Online Medical Literature Analysis and Retrieval System (MEDLINE®), Latin American and Caribbean Literature in Health Sciences ( LILACS), Nursing Database (BDENF). The keywords used followed the description of the terms Health Science Descriptors (DeCS) and Medical Subject Heading (MESH) in Portuguese, which are: visual acuity, elderly. In order to carry out the integrated search, the “and” connective was used, uniting the descriptors. At this stage, there was no use of other filters in order to address all the available literature within the focus of interest. Results: Initially, a table was built to expose the studies containing information such as year, title, authors and place of publication. After searching the databases through the established inclusion and exclusion descriptors, 08 articles were selected in (Chart 1) for analysis of the integrative review. Conclusion: Given the studies pointed out in the research, it can be seen that the quality of life of elderly patients is directly linked to the quality of vision. Visual acuity assessment is a way to detect possible pathologies and even a way to prevent the appearance of factors that can trigger vision loss, which can lead to musculoskeletal injuries due to falls.